2, 2, 2‐Trifluoroethyl Oxalates in the One‐Pot Parallel Synthesis of Hindered Aliphatic Oxamides1. Issue 12 (30th March 2016) - Bogolubsky, Andrey V.; Moroz, Yurii S.; Mykhailiuk, Pavel K.; Pipko, Sergey E.; Grishchenko, Alexander V.; Zhemera, Anton V.; Konovets, Anzhelika I.; Doroschuk, Roman A.; Dmytriv, Yurii V.; Zaporozhets, Olga A.; Tolmachev, Andrey
Abstract: A simple parallel synthesis approach to unsymmetrical N 1, N 2 ‐substituted aliphatic oxamides using methyl (2, 2, 2‐trifluoroethyl) oxalate and bis(2, 2, 2‐trifluoroethyl) oxalate was developed. The method was validated on a 52‐membered set of the oxamides, derived mainly from hindered primary and secondary aliphatic amines, and gave the products with a high overall success rate in moderate yields. Abstract : An approach to the synthesis of alkyl oxamides from hindered amines using trifluoroethyl oxalates was developed. Validation of the method on a millimolar scale gave the oxamides in multi‐milligram quantities.